Harnessing the Role of Three Lactic Acid Bacteria (LAB) Strains for Type II Sourdough Production and Influence of Sourdoughs on Bread Quality and Maillard Reaction Products - Sahin, Mustafa; Ozgolet, Muhammed; Cankurt, Hasan; Dertli, Enes (MDPI, 2024)
This study tested the effect of Companilactobacillus paralimentarius E-106, Lactiplantibacillus paraplantarum N-15 and Lactiplantibacillus plantarum SC-9 on the amount of Maillard reaction and aroma profile in bread making with main bread quality parameters. The specific volumes of sourdough and control breads were in the range of 2.97-3.04 cm3/g, and the control II bread had the highest hardness values on all days. The FAST index value was determined to be between 40.48% and 81.22% in all breads. The FAST index value was found to be higher in the control breads than in the sourdough breads. In the volatile compounds analysis, 72 volatile compounds were detected. The variety of volatile compounds in the breads with sourdough addition was higher than the control breads. Among the tested strains, Companilactobacillus paralimentarius E-106 demonstrated superior properties for bread characteristics in comparison to other strains as a type II sourdough starter. In summary, improved aroma profile and decreased Maillard reaction products can be provided by sourdough addition without changing the bread quality, along with meeting consumer demand for less additive use.
Keywords: sourdough bread; lactic acid bacteria; aroma profile; FAST index; Maillard reaction; SENSORY PROPERTIES; WHEAT BREAD; IMPACT; FLOUR; OPTIMIZATION; INGREDIENTS; VOLATILES; STARTER; STORAGE; YEASTS; Food Science & Technology